The impact of enhancing publicity and commemoration of body donors at Zhengzhou University, China - Zhang, Shiqiang; Wang, Jiannan; Zhang, Jingjing; Xu, Gaolei; Zhang, Zhenhua; Wang, Yongkui; Chang, Cheng; Chen, Xuemei; Li, Ming; Cao, Jing; Zang, Weidong (Anatomical sciences education, 2023)
As a fundamental subject of medical education, human anatomy plays a critical role in the development of medical science. However, because of multiple factors including cultural conservativism and limited social understanding, China is facing a particularly severe shortage of bodies donated for anatomy education. Zhengzhou University (ZZU) has continued to uphold whole‐body dissection as the preferred method for medical students to learn anatomy. For this study, records of registered individuals (who have signed a body donation agreement) and donors (whose bodies have been received) from 2001 to 2020 were collected and analyzed. The aim of this study was to explore the factors influencing the body donation program (BDP) at ZZU, and then reinforce the social understanding for the BDP. The results showed a significant increase in the numbers of both registered individuals and donors since 2015, which is the year the publicity and commemoration in honor of donors were increased. There were no significant differences between the biological male and female sexes in the registered individuals, but the number of male donors (12.85 ± 10.86, per year) was significantly higher than that of female donors (4.75 ± 4.53, per year). The current donor profile at ZZU is male in his 60/70s, while the profile of registered individuals is male or female in their 60s. Strengthening the publicity and commemoration in honor of donors may contribute to the implementation of BDPs.